Impaired skin regeneration and remodeling after cutaneous injury and chemically induced hyperplasia in taps-transgenic mice - Hildenbrand, Maike; Rhiemeier, Verena Margrit; Hartenstein, Bettina; Lahrmann, Bernd; Grabe, Niels; Angel, Peter; Heß, Jochen (The journal of investigative dermatology, 2010)
Recently, we identified an AP-1-dependent target gene in 12-O-tetradecanoylphorbol-13-acetate (TPA)-treated mouse back skin, which encodes a retroviral-like aspartic proteinase (Taps/Asprv1). Taps expression was detected almost exclusively in stratified epithelia of mouse embryos and adult tissues, and enhanced protein levels were present in several non-neoplastic human skin disorders, implicating a crucial role for differentiation and homeostasis of multilayered epithelia. Here, we generated a mouse model in which Taps transgene expression is under the control of the human ubiquitin C promoter (UBC-Taps). Although no obvious phenotype was observed in normal skin development and homeostasis, these mice showed a significant delay in cutaneous wound closure compared with control animals. Shortly after re-epithelialization, we found an increase in keratinocytes in the stratum granulosum, which express Filaggrin, a late differentiation marker. A hypergranulosum-like phenotype with increased numbers of Filaggrin-positive keratinocytes was also observed in UBC-Taps mice after administration of TPA. In summary, these data show that aberrant Taps expression causes impaired skin regeneration and skin remodeling after cutaneous injury and chemically induced hyperplasia.
Gesehen am 10.05.2023